Science journalism in pandemic times: perspectives on the science-media relationship from COVID-19 researchers in Southern Europe - Marín-González, Esther; Navalhas, Inês; Dijkstra, Anne M.; De Jong, Anouk; Luís, Cristina (Frontiers in Communication, 2023)
Several studies have investigated the relationship between scientists and journalists. However, Southern Europe has been less studied when it comes to understanding the nature and effectiveness of collaborations between these two groups of professionals. To address this gap, this study focused on researchers (i.e., academics and scientists from different fields, including clinical researchers and medical doctors) who conducted research activities on COVID-19-related topics in three Southern European countries (Italy, Portugal, and Spain). Using an approach that combined survey data (n=317) with semi-structured interviews (n=40), we explored researchers’ personal beliefs, opinions, and experiences regarding their encounters with the media during the pandemic. Our results show that researchers’ motivations, concerns, and benefits in their interactions with the media remained largely unchanged during the pandemic. Despite the additional challenges posed by the health emergency, most researchers in Italy, Portugal, and Spain rated their interactions with journalists positively. Several practices to promote and maintain trustful and fruitful cooperation with journalists were also identified. Additionally, lessons learned were extracted from the interactions between researchers and journalists during the pandemic. They hold particular relevance in a context of uncertainty, fake news, high demand for information and high expectations in science and technology. These findings aim to support both the scientific community and media professionals to deal with current and future communicative challenges such as health, environmental and social crises that require joint efforts from multiple societal actors.